The immunology of brain tumors: cancer immunology - Bunse, Lukas; Bunse, Theresa; Kilian, Michael; Quintana, Francisco J.; Platten, Michael (Science immunology, 2025)
Brain tumors represent a unique challenge for cancer immunotherapies because of their location in an immune privileged site. However, the brain tumor immune microenvironment is dictated more by tumor type than the location within the brain per se. This feature is reflected by the higher immunogenicity and response to immunotherapies of metastatic brain tumors compared with primary brain tumors. Immunotherapies for brain tumors aim at inducing and boosting tumor T cell responses using vaccines, immune checkpoint inhibitors, or adoptive T cell therapies. A fundamental challenge in the field is how such brain tumor-targeting T cells gain access to brain tumors and maintain their function despite a hostile immunosuppressive microenvironment. Here, we review current knowledge of the cellular and molecular determinants of the antigenicity of brain tumors and the immunosuppressive brain tumor microenvironment. Expanding and exploiting this knowledge will provide the key for effective combinatorial therapies.
Gesehen am 05.01.2026